Evaluasi Laporan Kinerja Keuangan PT Antam Tbk Menggunakan Analisis Trend pada Periode 2020-2023 - Vella Adelia; Hanum Nur Rahmadhani; Nelsy Helmilia Putri; Ela Juliyani; Wanda Berliandes; Rahma Maulida Erizal; Annisa Safitra; Putri Fauzely Mulia; Raja Septian Armel; Billy Nurmanto (Universitas Maritim AMNI Semarang, 2024)
Trend analysis is an analysis that compares more than 2 periods of financial statements. PT Antam Tbk is one of the largest mining companies in Indonesia. The purpose of this study was to determine the results of the evaluation of the financial performance report of PT Antam Tbk using trend analysis in the period 2020 to 2023. The research method used is quantitative descriptive method, which involves processing the company's financial data that is already available in the form of financial statements. This study uses secondary data in collecting information. The results of this study concluded that PT Antam Tbk succeeded in increasing the value of assets and equity, and decreasing the value of liabilities. As for the income statement, the company managed to increase profit after income tax by 167.7% from the period 2020 to 2023.